Patterns of less-than-full-time working by NHS consultants - Elaine Kelly; George Stoye; Max Warner (Institute for Fiscal Studies (IFS), 2023)
The 2020 NHS People Plan committed to providing flexible working opportunities to all NHS staff. An important component of flexible working is less-than-full-time (LTFT) working, enabling staff to balance paid work with other commitments. However, there is currently only limited empirical evidence on the extent to which different staff groups work LTFT across the NHS. This report uses the Electronic Staff Record (ESR), the monthly payroll of all staff directly employed by NHS hospitals in England, to examine the patterns of LTFT working by consultants in NHS acute trusts. We first consider how the prevalence of LTFT working among consultants has changed over time, how it varies by age and gender, and the extent to which changes to the demographic composition of the consultant workforce explain changes over time to LTFT working rates. We then examine how patterns of LTFT working vary across NHS trusts, regions and clinical specialties. One particular area of interest for policymakers is how LTFT work interacts with, precedes and potentially delays consultants leaving the NHS. This is especially true for older, more experienced consultants, who may reduce their working hours prior to full retirement. We therefore also document how LTFT working interacts with leaving the NHS acute sector by examining how working patterns change in the four years leading up to consultants leaving the NHS acute sector, and how these patterns differ between older and younger consultants.
Keywords: 330; Employment and income; Health and social care; Healthcare; Employment; Labour supply and workforce; NHS; Public sector